2010
DOI: 10.5194/acp-10-8151-2010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the aerosol direct radiative effect by semi-volatile aerosol components: airborne measurements in North-Western Europe

Abstract: Abstract.A case study of atmospheric aerosol mea-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 74 publications
(89 reference statements)
8
110
0
Order By: Relevance
“…9a) were uncorrelated (R 2 = 0.14), while γ and Fo (OM / (OM + NO Yangtze River Delta) (Shi et al, 2014) and Beijing (Sun et al, 2012). This may partly result from the increasing availability of NH 3 to form NH 4 NO 3 (Morgan et al, 2010) due to the decrease of SO 2 . The Chinese government has put an emphasis on the control of SO 2 emissions in recent years, and desulfurization technology has been installed at coal-fired power units as well as certain steel and cement production facilities.…”
Section: The Relationship Of Scattering Enhancement Factor With Chemimentioning
confidence: 94%
“…9a) were uncorrelated (R 2 = 0.14), while γ and Fo (OM / (OM + NO Yangtze River Delta) (Shi et al, 2014) and Beijing (Sun et al, 2012). This may partly result from the increasing availability of NH 3 to form NH 4 NO 3 (Morgan et al, 2010) due to the decrease of SO 2 . The Chinese government has put an emphasis on the control of SO 2 emissions in recent years, and desulfurization technology has been installed at coal-fired power units as well as certain steel and cement production facilities.…”
Section: The Relationship Of Scattering Enhancement Factor With Chemimentioning
confidence: 94%
“…Airborne measurements revealed complex partitioning of the semi-volatile aerosol components in the planetary boundary layer. Measurements revealed an increase in secondary aerosol mass with an increasing altitude in the boundary layer, causing an increase of the aerosol direct radiative forcing (Morgan et al, 2010a). Specifically, in-situ measurements in the vicinity of a ground-based measurement site at Cabauw, the Netherlands, showed that ammonium nitrate was the dominant chemical component aloft, while at the ground OA dominated.…”
Section: Sub-micron Aerosol Chemical Compositionmentioning
confidence: 99%
“…While the M 30 may be due to nitro-aromatics that have been associated with biomass burning (Mohr et al, 2013), the vertical trends presented here do not match with the rBC, so it is not thought to be the case here. The structure in B744-5 is probably due to the ammonium nitrate present during these flights, which will peak in concentration at the top of the boundary layer (Morgan et al, 2010a;Morgan et al, 2009) and suppress the ratio through an inorganic NO + contribution to M 30 .…”
Section: Vertical Structurementioning
confidence: 99%
“…The positive gradient through the boundary layer (featuring a doubling of Org 82 from 20 to 40 ng m −3 ) could be as a result of the repartitioning of semivolatile material into the aqueous phase due to the reduced temperature and increased particulate water content (Morgan et al, 2010a). This would be consistent with the observations of Fu et al (2010), who found an increase in isoprene SOA tracers at night-time at an elevated site in China, and the modelling work of Henze and Seinfeld (2006), who predict enhanced partitioning to the particle phase at higher altitudes.…”
Section: Boundary Layer Profilementioning
confidence: 99%